Transitional changes in the mucosa adjacent to the colorectal carcinoma- A SEM study - Ansari, Reshma.M.; Tun, Ye; Md Nor, Azmi; Myint, Yi Yi (Universiti Putra Malaysia, 2012)
Colorectal cancer is the fourth most common cancer worldwide, with about 677,000 deaths each year. The term transitional mucosa™ was coined by Filipe in 1969 to describe alterations in the morphology and mucin histochemistry of the large intestinal mucosa immediately adjacent to colorectal adenocarcinomas. The TM is considered as an important prognostic marker for patients with large bowel cancer following radical resection because patients with retained TM have a poorer prognosis. 3 samples from the proximal margin of a resected colorectal surgical specimen were taken to study the extent of the transitional changes in them. They were selected approximately 2cms, 5cms and 10cms away from the tumor site. The tissues were then processed and viewed under Scanning Electron microscope (SEM) to gauge the extent of the transitional changes. These changes were compared with the normal colon samples taken from normal patients. Transitional changes were found both near as well as farther away from the tumor and were characterized.